Dual FISH analysis of benign and malignant tumors of the salivary glands and paranasal sinuses - Götte, Karl; Ganßmann, Stephan; Affolter, Annette; Schäfer, Carsten; Riedel, Frank; Arens, Norbert; Finger, Sonja; Hörmann, Karl (Oncology reports, 2005)
To date, the underlying genomic changes in benign and malignant tumors of salivary-gland and paranasal-sinus origin are poorly understood. This is due in part to the low incidence of these tumors and the enormous histological variety of tumors within this head and neck region. We examined 58 of these tumors (14 adenoid cystic carcinomas, 9 adenocarcinomas, 5 cylindrical carcinomas, 11 pleomorphic adenomas, and 19 inverted papillomas) by dual fluorescence in situ hybridization (FISH) with centromere-specific probes on six chromosomes (3, 7, 9, 11, 17, and 18) for numerical changes. In adenoid cystic carcinomas, monosomy of chromosome 17 and polysomy of chromosomes 3, 9 and 11 were most frequently encountered. In adenocarcinomas, monosomy of chromosome 17 and polysomy of chromosomes 7 and 11 were most frequent. In cylindrical cell carcinomas, polysomy of chromosomes 7, 9, 11 and 17 was present in the majority of tumors. Disomy is rare, even in benign tumors. Polysomy is more frequent in malignant tumors than in benign. Tetrasomy is found almost only in malignant tumors. In summary, the occurrence of polysomy might reflect a step towards malignancy in tumors of the salivary glands and paranasal mucosa. Polysomy of chromosome 11 could be defined as typical for all investigated histological types of malignant tumor in this region of the head and neck.